2020
DOI: 10.3390/ijerph17165983
|View full text |Cite
|
Sign up to set email alerts
|

How Does Part-Time Farming Affect Farmers’ Adoption of Conservation Agriculture in Jianghan Plain, China?

Abstract: Part-time farming has been suggested by scholars to play an important part in farmers’ decision making, but seldom empirical evidence has been done on the field of conservation agriculture (CA) technology adoption worldwide. Based on the field survey data of 433 farmers in Jianghan Plain, China, this paper estimate the impact of part-time farming on farmers’ adoption of CA technology by applying the multivariate logistic model. The results show that 91.92% of the farmers adopted CA technology. Part-time farmin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…Although farmers in Angonia County practice CA techniques at all times, they do apply these techniques to only ¼ of their fields, mainly because of a lack of economic resources for CA inputs such as herbicides. Yang & Sang, (2020) have also observed that poorresource farmers restrict the adoption of CA technology because of economic conditions. Farmers may also refuse to adopt certain aspects of technology due to a lack of labour, a lack of land on which to implement the technology, an uneasy technology operation or a lack of better approach to communicating the three principles of CA to farmers.…”
Section: Factors Influencing the Use Of Conservation Adoption Technol...mentioning
confidence: 99%
“…Although farmers in Angonia County practice CA techniques at all times, they do apply these techniques to only ¼ of their fields, mainly because of a lack of economic resources for CA inputs such as herbicides. Yang & Sang, (2020) have also observed that poorresource farmers restrict the adoption of CA technology because of economic conditions. Farmers may also refuse to adopt certain aspects of technology due to a lack of labour, a lack of land on which to implement the technology, an uneasy technology operation or a lack of better approach to communicating the three principles of CA to farmers.…”
Section: Factors Influencing the Use Of Conservation Adoption Technol...mentioning
confidence: 99%
“…However, according to Czyzewski et al (2021), the more crucial the traditional production factors are, the more crucial the human factor is for the adoption of innovation. Although the role of the human factor is relatively less analysed in agricultural studies than economic factors, there are fruitful studies on the effects of socio-demographic characteristics such as age, gender, education level and income level (Alam et al, 2010;Mwangi & Kariuki, 2015;Ntshangase et al, 2018;Yang & Sang, 2020) on adoption behaviour. For example, according to Czyzewski et al (2021), human capital, conceptualised in relation to abilities and skills and whose driving forces are education and training, plays a significant role in farmers' adoption behaviour by improving their decision-making capacity.…”
Section: Theoretical Background and Literature Reviewmentioning
confidence: 99%
“…(2021), the more crucial the traditional production factors are, the more crucial the human factor is for the adoption of innovation. Although the role of the human factor is relatively less analysed in agricultural studies than economic factors, there are fruitful studies on the effects of socio‐demographic characteristics such as age, gender, education level and income level (Alam et al., 2010; Mwangi & Kariuki, 2015; Ntshangase et al., 2018; Yang & Sang, 2020) on adoption behaviour. For example, according to Czyzewski et al.…”
Section: Theoretical Background and Literature Reviewmentioning
confidence: 99%
“…They have a large rice planting area, superior water conservancy conditions, and good conditions for agricultural development. Agricultural science and technology demonstration farms that used pesticide control techniques and deep tillage are vigorously constructed in Yicheng, with one of the largest parks taking up approximately 80 hm 2 , in which the use of fertilizer decreased by 10% annually during 2017-2019 [25].Jingshan is the birthplace of Chinese farming culture and unique production bases of high-quality rice (named as Guo Bao Qiao Mi). Straw returning to field, no-till, and less-tillage are the three main conservation tillage types applied in Jingshan County.…”
Section: Study Areamentioning
confidence: 99%